A case of penta X syndrome caused by nondisjunction in maternal meiosis 1 and 2. Issue 7 (1st June 2017) - Markholt, Sara; Graakjaer, Jesper; Thim, Signe Bødker; Høst, Bente; Skytte, Anne‐Bine
Key Clinical Message: The prenatal abnormalities in patients with penta X syndrome appear late in pregnancy and are nonspecific. In contrast, the postnatal phenotype is well described although new findings are still revealed. Penta X syndrome is a result of successive nondisjunctions of the X chromosomes in both maternal meiotic divisions. Abstract : The prenatal abnormalities in patients with penta X syndrome appear late in pregnancy and are nonspecific. In contrast, the postnatal phenotype is well described although new findings are still revealed. Penta X syndrome is a result of successive nondisjunctions of the X chromosomes in both maternal meiotic divisions.